2006
DOI: 10.1038/sj.hdy.6800881
|View full text |Cite
|
Sign up to set email alerts
|

Cardinium symbionts cause cytoplasmic incompatibility in spider mites

Abstract: Intracellular symbiotic bacteria belonging to the CytophagaFlavobacterium-Bacteroides lineage have recently been described and are widely distributed in arthropod species. The newly discovered bacteria, named Cardinium sp, cause the expression of various reproductive alterations in their arthropod hosts, including cytoplasmic incompatibility (CI), induction of parthenogenesis and feminization of genetic males. We detected 16S ribosomal DNA sequences similar to those of Cardinium from seven populations of five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
182
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(187 citation statements)
references
References 39 publications
2
182
0
3
Order By: Relevance
“…This is concordant with the female mortality type of CI (Breeuwer, 1997; Vavre B. sarothamni is the third host species in which Cardiniuminduced CI is observed, and this study reveals the strongest CI effect found for Cardinium so far. The other two studies on Cardinium CI found incomplete CI expression; in the parasitoid wasp E. pergandiella, 87% fewer daughters were produced in incompatible crosses, and in the spider mite E. suginamensis, this was 46% (Hunter et al, 2003;Gotoh et al, 2006). Female mortality is the only CI type found for Cardinium so far (Hunter et al, 2003;Gotoh et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is concordant with the female mortality type of CI (Breeuwer, 1997; Vavre B. sarothamni is the third host species in which Cardiniuminduced CI is observed, and this study reveals the strongest CI effect found for Cardinium so far. The other two studies on Cardinium CI found incomplete CI expression; in the parasitoid wasp E. pergandiella, 87% fewer daughters were produced in incompatible crosses, and in the spider mite E. suginamensis, this was 46% (Hunter et al, 2003;Gotoh et al, 2006). Female mortality is the only CI type found for Cardinium so far (Hunter et al, 2003;Gotoh et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cardinium and Wolbachia have been found coinfecting the same host species (Weeks et al, 2003;Zchori-Fein and Perlman, 2004;Gotoh et al, 2006;Duron et al, 2008). Although both Cardinium and Wolbachia can manipulate their host's reproductive system, little is known about their interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of infected females with uninfected males and other closely related species, revealed that Cardinium does not have a negative effect on the fitness of B. californicus. The bacterium has also been found in a population of Eotetranychus suginamensis in Japan (Gotoh, Noda, & Ito, 2006). One species of spider mite, Eotetranychus pueraricola harbored both Cardinium and Wolbachia, but these symbionts seemed to have no effect on the reproduction of the host.…”
Section: Serratia Marcescensmentioning
confidence: 90%
“…Recently, a high incidence (22%) has been detected in spiders (Araneae) (Duron et al, 2008). Like Wolbachia, in the a-Proteobacteria, Cardinium may cause manipulation of host reproduction in ways that increase its frequency within a host population, including feminization (genotypic males develop as functional phenotypic females) (Weeks et al, 2001), cytoplasmic incompatibility (Hunter et al, 2003;Gotoh et al, 2007) and thelytokous parthenogenesis (females produce only daughters from unfertilized eggs) (Zchori-Fein et al, 2001, 2004Provencher et al, 2005;Groot and Breeuwer, 2006;Matalon et al, 2007). Cardinium also increases the fecundity of a mite host (Weeks and Stouthamer, 2004).…”
Section: Introductionmentioning
confidence: 99%